Exames anatomopatológicos em animais selvagens - Pimenta, Lucas Braga [UNESP] (2015)
The necropsy and histopathology in non domestic animals, from wild or captivity, is an important material for various purposes, such as study of anatomy, biology, food habits, parasitism, their diseases, etiologic agent, etc. From the carcasses of these animals can be mounted skeletons and skins (taxidermy) for use in museums, schools, environmental education, among others. From the study of etiologic agents and existing vectors, studies can be done to verify the participation of these animals in the epidemiology as reservoir or as host, of many diseases that affect both, captive or free wild animals, as well domestic animals and humans. Finally this study aims to contribute to "One Health", considering the health of the environmental, animal and human. In addition, the results of the necropsy and histopathology exam sent to the owners provide information for the treatment, prevention, control of the detected diseases.